Who Wants to Be an Intrapreneur? Relations between Employees’ Entrepreneurial, Professional, and Leadership Career Motivations and Intrapreneurial Motivation in Organizations - Chan, Kim-Yin; Ho, Moon-Ho R.; Kennedy, Jeffrey C.; Uy, Marilyn A.; Kang, Bianca N. Y.; Chernyshenko, Olexander S.; Yu, Kang Yang T. (Frontiers in Psychology, 2017)
This paper reports an empirical study conducted to examine the relationship between employees’ Entrepreneurial, Professional and Leadership (EPL) career motivations and their intrapreneurial motivation. Using data collected from 425 working adults in the research/innovation and healthcare settings, we develop a self-report measure of employee intrapreneurial motivation. We also adapt an existing self-report measure of E, P and L career motivations (previously developed and used with university students) for use with working adult organizational employees. Confirmatory factor analysis indicate that E, P and L motivations and intrapreneurial motivation can be measured independently and reliably, while regression analyses show that the employees’ E, P and L motivations all contribute to explaining variance in their intrapreneurial motivation. Individuals with high E, P and L motivational profiles are also found to have the highest intrapreneurial motivation scores, while those low on E, P and L motivations have the least intrapreneurial motivation. Our findings suggest that the potential for intrapreneurship is not unique to only entrepreneurial employees. Instead, one can find intrapreneurs among employees with strong leadership and professional motivations as well. We discuss the findings in the context of generating more research to address the challenges of talent management in 21st century knowledge economies where there is greater career mobility and boundarylessness in the workforce.